(untitled) (Biomedical Research and Therapy, 2018)
Chronic graft versus host disease (cGVHD) is a complex entity and major complication following allogenic hematopoietic stem cell transplantation (allo-HSCT). This study was the first to report oral manifestation and dental management in a patient with cGVHD after allo-HSCT with a longterm follow-up. A 40-year-old man referred to Department of Oral and Maxillofacial Medicine with complaints of tongue burning, mouth dryness, and ulcers. He had chronic myelogenous leukemia and had undergone allo-HSCT. The patient had undergone treatment with several sessions of extracorporeal photopheresis. The GVHD complications had started about nine months after HSCT. In conclusion, the dentist should play a role in the local therapy of cases with oral manifestation and dental management of cGVHD. Controlling the GVHD can reduce oral and dental alterations, increase the improvement of the quality of life, and reduce the need for more intensive immunosuppressive systemic therapies.